Greenhouse gas intensity of South Africa's production and consumption : a study of the relationship between economic growth, income distribution and greenhouse gas emission in South Africa - Piaget, Stève Marc (Department of Chemical Engineering, 2014)
Includes abstract. Includes bibliographical references.